ANALISIS SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION (STUDI PERSEPSI NASABAH BANK UMUM SYARIAH DI SURAKARTA) - Listyani Ninda Latifa; Iin Emy Prastiwi; Muhammad Tho’in (LP3M, 2024)
Bank Syariah in Indonesia has a good potential for growing gradually and being one of leading Islamic banks at the global level is wide-open. In addition to positive growth performance, climate support that the Indonesian government has a mission to create a halal industry ecosystem and have a large and strong national Islamic bank. Therefore, researchers want to analyze service quality on customer satisfaction of Bank Syariah (case study in Surakarta). The method used in this research is quantitative descriptive research method. The object of research is 150 customers of Bank Syariah in Surakarta. The data analysis method in this research is a questionnaire instrument test using customer satisfaction index (CSI) analysis technique. Based on research analysis, the CSI result is 83.53%. This value is in the range between 81.00-100.00 which means very satisfied. The conclusion is the customers are very satisfied with service quality of Bank Syariah in Surakarta. Hopefully Bank Syariah in Surakarta is able to keep their good service quality over their customers satisfaction. The author provides recommendations for further research to compare the servive quality of Bank Syariah in Surakarta between branch offices in order to find out and compare their service quality.